Modified metal organic framework material, method for preparing the same, and use thereof

CN119570046BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311146082.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2026-10-30
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了克服现有技术存在的N-取代吡咯化合物产品选择性低或催化剂需用到昂贵金属等问题,提供一种改性金属有机骨架材料及其制备方法和应用;本发明所述的改性金属有机骨架材料具有褶皱外表面,与水的接触角为40-120°;所述改性金属有机骨架材料用于催化制备N-取代吡咯化合物(例如2,5-二甲基-N-取代吡咯化合物)具有反应效率高、产物收率高等突出的特点

Benefits of technology

[0016]本发明所述改性金属有机骨架材料在制备过程中配位水分子很容易被除去,形成开放的金属中心作为催化中心;通过配体交换法,利用含苯环的多氮唑配体碱性较强,使金属有机骨架材料的孔表面性质较容易调控,氮原子给体参与配位,从而,相对于改性前,其具有一定的疏水性;新形成的金属开放位点提高了材料的酸量,新形成的介孔空腔有效的促进底物的扩散,不仅有利于底物吸附和产物脱附,增加了目标产物的收率,而且抑制了催化剂的失活。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570046B_ABST
    Figure CN119570046B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of MOFs materials, in particular to a modified metal organic framework material and a preparation method and application thereof. The modified metal organic framework material comprises: a metal center; and at least two kinds of organic ligands coordinated with at least two combination sites of the metal center to form an at least partially crystallized network structure with multiple internal pores; wherein the modified metal organic framework material crystal has a wrinkled outer surface, and the contact angle of the modified metal organic framework material with water is 40-120 degrees. The modified metal organic framework material is used for catalytically preparing N-substituted pyrrole compounds (for example, 2,5-dimethyl-N-substituted pyrrole compounds), and has the outstanding characteristics of high reaction efficiency and high product yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of MOF materials technology, specifically to a modified metal-organic framework material, its preparation method, and its application. Background Technology

[0002] Metal-organic frameworks (MOFs) are crystalline materials that self-assemble with metal ions or metal ion clusters as nodes and organic bridging ligands containing carboxylic acids or nitrogen through coordination bonds to form periodically arranged network frameworks. Due to their diverse structural compositions, high specific surface area and porosity, as well as tunable pore structure and size, they have broad application prospects in fields such as gas storage and separation, luminescence and detection, catalysis, and drug delivery and controlled release.

[0003] From the study of bulk MOF materials to nanoscale or two-dimensional morphologies, from exploring the porosity of MOF materials themselves to constructing hierarchical pores, and from the preparation of single MOF materials to the synthesis of MOF composites, the overall trend is a process of moving from bulk to miniaturization, nanoscale, or further structural development; and from single to diversified structures.

[0004] Nitrogen-containing heterocycles, especially functionalized pyrroles, are important structural units in a large number of naturally occurring and pharmacologically active molecules, and are widely used in the core structures of bioactive substances such as vitamins, anticancer drugs, and antibacterial drugs. The main traditional pathways for N-substituted pyrroles typically use substituted ketones, aldehydes, or amines as substrates, most of which are derived from petrochemical resources, and the reaction yields are relatively low. Exploring the construction of pyrrole derivatives based on biomass is therefore more important. 2,5-Hexanedione (HDO) has attracted increasing attention as an important biomass platform compound, and researchers have synthesized HDO through cellulose or sugar platforms. HDO can undergo Paal-Knorr condensation reactions with amines or nitro compounds under appropriate catalysts to generate N-substituted pyrroles, achieving high selectivity and yield under suitable catalysts and reaction conditions.

[0005] Existing technologies [Nat. Chem. 2013, 5, 140-144; Catal. Sci. Technol. 2014, 4, 4188-4192] have pioneered heterogeneous catalytic dehydrogenation coupling reactions of bio-secondary alcohols and amino alcohols, which have become an important method for constructing pyrrole skeletons. Despite the high yields, the costly and potentially toxic iridium species require separation and recovery, posing a challenge to establishing greener and more sustainable synthetic methods. Summary of the Invention

[0006] The purpose of this invention is to overcome the problems of low selectivity of N-substituted pyrrole compounds or the need for expensive metal catalysts in existing technologies, and to provide a modified metal-organic framework material, its preparation method, and its application. The modified metal-organic framework material of this invention has a wrinkled outer surface and a water contact angle of 40-120°. The modified metal-organic framework material is used to catalyze the preparation of N-substituted pyrrole compounds (e.g., 2,5-dimethyl-N-substituted pyrrole compounds) with outstanding characteristics such as high reaction efficiency and high product yield.

[0007] To achieve the above objectives, a first aspect of the present invention provides a modified metal-organic framework material, the modified metal-organic framework material comprising:

[0008] Metal center; and

[0009] At least two organic ligands coordinated to at least two binding sites of the metal center to form a network structure with at least partial crystallization and multiple internal pores;

[0010] The modified metal-organic framework material crystal has a wrinkled outer surface, and the contact angle between the modified metal-organic framework material and water is 40-120°.

[0011] A second aspect of the present invention provides a method for preparing the modified metal-organic framework material of the present invention, the method comprising the following steps:

[0012] S1. Dissolve the soluble metal salt and the first organic ligand in solvent I, crystallize, separate, and perform a first drying to obtain the MOF material formed by the metal and the first organic ligand;

[0013] S2. Contact the MOFs material from step S1 with a solution containing a second organic ligand and an alkaline substance; separate, wash, and perform a second drying to obtain the modified metal-organic framework material.

[0014] A third aspect of this invention provides the application of the modified metal-organic framework material described herein in the preparation of N-substituted pyrrole compounds.

[0015] Through the above technical solution, the modified metal-organic framework material of the present invention has a wrinkled outer surface and a water contact angle of 40-120°. Compared with the original material, it has a certain degree of hydrophobicity. According to the preferred embodiment of the present invention, compared with the original material, the modified metal-organic framework material of the present invention increases the acid content and forms a new mesoporous cavity.

[0016] In the preparation process of the modified metal-organic framework material described in this invention, coordinated water molecules are easily removed, forming open metal centers as catalytic centers. Through ligand exchange, the strong basicity of polyazole ligands containing benzene rings makes it easier to control the pore surface properties of the metal-organic framework material. Nitrogen atom donors participate in coordination, thus, compared with the unmodified material, it has a certain degree of hydrophobicity. The newly formed open metal sites increase the acidity of the material, and the newly formed mesoporous cavities effectively promote substrate diffusion, which not only facilitates substrate adsorption and product desorption, increasing the yield of the target product, but also inhibits catalyst deactivation.

[0017] The modified metal-organic framework material described in this invention is used for the catalytic preparation of N-substituted pyrrole compounds (e.g., 2,5-dimethyl-N-substituted pyrrole compounds), achieving high reaction efficiency and high product yield. This method provides new ideas for the green synthesis of pyrrole compounds and offers a new direction for metal-organic framework materials in the field of biomass catalysis, achieving unexpected technical results. Attached Figure Description

[0018] Figure 1 The images are scanning electron microscope (SEM) images of Cu-BTC and Cu-BTC-BzIm from Example 1.

[0019] Figure 2 The image shows the pyridine desorption infrared (Py-FTIR) images of Cu-BTC and Cu-BTC-BzIm in Example 1.

[0020] Figure 3 The contact angle between Cu-BTC and water in Example 1;

[0021] Figure 4 The contact angle between Cu-BTC-BzIm and water in Example 1;

[0022] Figure 5 The N2- adsorption / desorption curves of Cu-BTC and Cu-BTC-BzIm in Example 1 are shown.

[0023] Figure 6 This is a scanning electron microscope (SEM) image of Cu-BTC-BzIm-2 in Example 2. Detailed Implementation

[0024] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0025] In this invention, the metal center refers to the metal ion used to form the coordination complex in MOF materials.

[0026] A first aspect of this invention provides a modified metal-organic framework material, the modified metal-organic framework material comprising:

[0027] Metal center; and

[0028] At least two organic ligands coordinated to at least two binding sites of the metal center to form a network structure with at least partial crystallization and multiple internal pores;

[0029] The modified metal-organic framework material crystal has a wrinkled outer surface, and the contact angle between the modified metal-organic framework material and water is 40-120°. The modified metal-organic framework material of this invention has a wrinkled outer surface and a contact angle with water of 40-120°, exhibiting a certain degree of hydrophobicity compared to its unmodified form.

[0030] According to a preferred embodiment of the present invention, the contact angle between the modified metal-organic framework material and water is 40-100°.

[0031] According to a preferred embodiment of the present invention, the modified metal-organic framework material has clusters of sheet-like protrusions distributed on the crystal surface to form a wrinkled outer surface.

[0032] According to a preferred embodiment of the present invention, the total acidity of the modified metal-organic framework material is 30-500 μmol·g. -1 Preferably, it is 40-400 μmol·g -1 .

[0033] According to a preferred embodiment of the present invention, the modified metal-organic framework material has a total specific surface area of ​​900-1800 m². 2 ·g -1 External specific surface area is 40-200m² 2 ·g -1 .

[0034] According to a preferred embodiment of the present invention, the total pore volume of the modified metal-organic framework material is 0.4-1.0 cm³. 3 ·g -1 The micropore volume is 0.2-0.9 cm³. 3 ·g -1 .

[0035] In this invention, the total pore volume of the modified metal-organic framework material is the sum of the micropore volume and the mesopore volume.

[0036] In this invention, the range of metals that can be selected for the metal center is relatively wide. According to a preferred embodiment of this invention, the metal of the metal center is selected from at least one of Zn, Zr, V, Cr, Fe, Co, Ni, Cu, Ag, Cd and Al, and preferably at least one of Zn, Cu, Ni, Fe, Co and Zr.

[0037] According to a preferred embodiment of the present invention, the organic ligand includes a first organic ligand and a second organic ligand, wherein the first organic ligand is selected from at least one of carboxylic acid organic ligands; and the second organic ligand is selected from at least one of polyazole organic ligands containing a benzene ring.

[0038] According to a preferred embodiment of the present invention, the first organic ligand is selected from at least one of pyromellitic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalenedicarboxylic acid, biphenyl dicarboxylic acid, and 3,3,5,5-biphenyltetracarboxylic acid.

[0039] According to a preferred embodiment of the present invention, the second organic ligand is selected from at least one of benzimidazole, 2-methylbenzimidazole, 5,6-dimethylbenzimidazole, 2-(2-hydroxybenzyl)benzimidazole, 2-aminobenzimidazole and 2-(4'-thiazole)benzimidazole.

[0040] Modified metal-organic framework materials possessing the aforementioned features of this invention can all achieve the objectives of this invention, and there are no special requirements for their preparation methods. In accordance with a preferred embodiment of this invention, this invention provides a method for preparing the modified metal-organic framework material of this invention, the method comprising the following steps:

[0041] S1. Dissolve the soluble metal salt and organic ligand I in solvent I, crystallize, separate, and first dry to obtain MOF material formed by metal and organic ligand I;

[0042] S2. Contact the MOFs material from step S1 with a solution containing organic ligand II and an alkaline substance; separate, wash, and perform a second drying to obtain the modified metal-organic framework material.

[0043] In the preparation process of the modified metal-organic framework material described in this invention, coordinated water molecules are easily removed, forming open metal centers as catalytic centers. Through ligand exchange, the strong basicity of polyazole ligands containing benzene rings makes it easier to control the pore surface properties of the metal-organic framework material. Nitrogen atom donors participate in coordination, thus, compared with the unmodified material, it has a certain degree of hydrophobicity. The newly formed open metal sites increase the acidity of the material, and the newly formed mesoporous cavities effectively promote substrate diffusion, which not only facilitates substrate adsorption and product desorption, increasing the yield of the target product, but also inhibits catalyst deactivation.

[0044] In this invention, there is no particular limitation on the type of soluble metal salt, such as soluble salts of metal nitrates, metal chlorides, metal sulfates, etc.

[0045] In this invention, the ratio of the soluble metal salt to the organic ligand I in step S1 can be selected over a wide range. According to a preferred embodiment of this invention, the molar ratio of the soluble metal salt to the organic ligand I is 1:0.2-5.

[0046] In this invention, the ratio of solvent I to soluble metal salt in step S1 can be selected from a wide range. According to a preferred embodiment of this invention, the ratio of solvent I to soluble metal salt is 5-100 mL solvent I / 1.0 g soluble metal salt.

[0047] In this invention, the ratio of MOF materials to organic ligand II in step S2 can be selected from a wide range. According to a preferred embodiment of this invention, the molar ratio of MOF materials to organic ligand II is 1:(0.01-5).

[0048] In this invention, the ratio of MOFs material to alkaline substance in step S2 can be selected from a wide range. According to a preferred embodiment of this invention, the molar ratio of MOFs material to alkaline substance is 1:(0.01-3).

[0049] In this invention, in step S2, the solvent in the solution containing organic ligand II and alkaline substance can be selected from a wide range. According to a preferred embodiment of this invention, the solvent is solvent II, which is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetone, dichloromethane, toluene, and ethylbenzene. Preferably, the mass ratio of MOFs material to solvent II is 1:(2-200).

[0050] In this invention, the range of alkaline substances that can be selected in step S2 is relatively wide, as long as they are organic bases or inorganic bases with weak alkalinity. According to a preferred embodiment of this invention, the alkaline substance is selected from at least one of triethylamine, trimethylamine, diisopropylethylamine, diethylamine, n-propylamine, n-butylamine, di-n-butylamine, ammonia, and aniline.

[0051] According to a preferred embodiment of the present invention, the organic ligand I is a first organic ligand.

[0052] According to a preferred embodiment of the present invention, organic ligand II is a second organic ligand.

[0053] According to a preferred embodiment of the present invention, the preparation method of the modified metal-organic framework material further includes, in step S2, immersing the washed solid in solvent III, wherein solvent III is selected from at least one of methanol, ethanol, dichloromethane and acetone; the preferred immersion conditions include: immersion temperature of 0-50°C; and mass ratio of solid to solvent III of 1:10-300.

[0054] In this invention, the soaking time can be determined according to actual needs. According to a preferred embodiment of this invention, the soaking time is 10-96 hours, and solvent III is replaced every 2-24 hours.

[0055] In this invention, the crystallization conditions in step S1 can be selected from a wide range. According to a preferred embodiment of this invention, the crystallization conditions include: a crystallization temperature of 30-200℃, preferably 50-160℃; and a reaction time that can be reasonably determined according to actual needs. Preferably, the crystallization time is 3-44h, preferably 5-24h.

[0056] In this invention, the range of selectable first drying conditions in step S1 is relatively wide. According to a preferred embodiment of this invention, the first drying conditions include: a drying temperature of 70-200℃; and a drying time that can be reasonably determined according to actual needs, which is 2-48h. Preferably, the drying is carried out in steps, with the first drying condition including: a temperature of 70-100℃ and a time of 1-24h; and the second drying condition including: a temperature of 120-200℃ and a time of 1-24h.

[0057] In this invention, the range of selectable contact conditions in step S2 is relatively wide. According to a preferred embodiment of this invention, the contact conditions include: a contact temperature of 30-180℃, preferably 50-110℃; and a contact time that can be reasonably determined according to actual needs, preferably 3-30h, preferably 6-20h.

[0058] In this invention, the range of selectable second drying conditions in step S2 is relatively wide. According to a preferred embodiment of this invention, the second drying conditions include: a drying temperature of 70-200℃; the drying time can be reasonably determined according to actual needs, preferably 2-48h; preferably, the drying is carried out in steps, with the first drying condition including: a temperature of 70-100℃ and a time of 1-24h; and the second drying condition including: a temperature of 120-200℃ and a time of 1-24h.

[0059] A third aspect of this invention provides the application of the modified metal-organic framework material described herein in the preparation of N-substituted pyrrole compounds. The modified metal-organic framework material described herein is used to catalyze the preparation of N-substituted pyrrole compounds (e.g., 2,5-dimethyl-N-substituted pyrrole compounds), achieving high reaction efficiency and high product yield.

[0060] This invention provides a method for preparing a 2,5-dimethyl-N-substituted pyrrole compound, the method comprising:

[0061] 2,5-hexanedione is contacted with amine compounds in the presence of a liquid diluent and a catalyst; the catalyst contains the modified metal-organic framework material described in this invention.

[0062] In this invention, the range of types of amine compounds that can be selected is relatively wide. According to a preferred embodiment of this invention, the amine compounds are selected from at least one of aniline, m-chloroaniline, p-methoxyaniline, 3-fluoroaniline, 3-methoxyaniline, m-toluidine, o-toluidine, n-butylamine, 3-nitroaniline, 4-nitroaniline, p-trifluoromethylaniline, p-hydroxyaniline, n-hexylamine, furfurylamine, naphthylamine, 2-thiophene methylamine, and benzylamine.

[0063] In this invention, there is no particular limitation on the type of liquid phase diluent, as long as it does not react with the substrate. Conventional liquid phase diluents in the art can be used in this invention. According to a preferred embodiment of this invention, the liquid phase diluent is selected from at least one of anhydrous methanol, anhydrous ethanol, propanol, isopropanol, n-butanol, toluene, cyclohexane, n-hexane, dichloromethane, tetrahydrofuran, acetone, and methyl isobutyl ketone.

[0064] In this invention, the ratio of 2,5-hexanedione to catalyst can be selected over a wide range. According to a preferred embodiment of this invention, the mass ratio of 2,5-hexanedione to catalyst is 1-100:1, preferably 2-30:1.

[0065] In this invention, the ratio of 2,5-hexanedione to amine compounds can be selected over a wide range. According to a preferred embodiment of this invention, the mass ratio of 2,5-hexanedione to amine compounds is 0.2-100:1, preferably 0.5-50:1.

[0066] In this invention, the ratio of liquid phase diluent to 2,5-hexanedione can be selected over a wide range. According to a preferred embodiment of this invention, the mass ratio of liquid phase diluent to 2,5-hexanedione is 0-200:1, preferably 5-50:1.

[0067] In this invention, the contact conditions between 2,5-hexanedione and amine compounds can be selected over a wide range. According to a preferred embodiment of this invention, the contact conditions include: a temperature of 100-220°C, preferably 120-200°C; and / or a time of 1-24h, preferably 4-20h.

[0068] In this invention, the N-substituted pyrrole compounds of the reaction product were qualitatively and quantitatively analyzed by gas chromatography-mass spectrometry (GC-MS), and the conversion rate of soluble carbohydrates in the product was analyzed by high-performance liquid chromatography (HPLC). The GC-MS system was an Agilent 7890A from Agilent Technologies, USA, with an HP-5 nonpolar capillary column (30m, 0.53mm). The gas chromatograph was an Agilent 7890B, with a flame ionization detector (FID) and an SE-54 capillary column (30m, 0.53mm). HPLC analysis was performed using an Agilent 1200 system with a SHODEX SC1011 sugar column (8×300mm).

[0069] The acid content and type of metal-organic framework materials were determined using the pyridine adsorption infrared method (Nicolet Model 710 spectrometer). The specific operational steps are as follows: a) Sample pretreatment: The sample (approximately 30 mg) was compressed into thin discs with a diameter of 13 mm and placed in the infrared sample cell. The sample was then pretreated in a vacuum chamber at 150 °C for 1 hour. After the sample cell cooled to room temperature, the infrared data of the sample was scanned as background. b) Pyridine adsorption: Pyridine vapor was introduced into the in-situ under room temperature and vacuum conditions until adsorption reached equilibrium, with an adsorption time of 1 hour. c) Pyridine desorption: After adsorption, a vacuum was applied at 100 °C until the internal pressure no longer changed, with a desorption time of 40 minutes. The infrared absorption spectra were then scanned and recorded. The difference spectrum before and after pyridine adsorption is the obtained pyridine adsorption-infrared absorption spectrum. The acid content of the sample was semi-quantitatively calculated based on the spectrum.

[0070]

[0071]

[0072] Where r and w are the diameter (cm) and mass (g) of the catalyst disc, respectively, and A is the integral value of absorbance at a specified wavenumber peak based on the scanned pyridine adsorption-infrared absorption spectrum. IMEC is the integral molar extinction coefficient, with IMECL being 2.22 and IMECB being 1.67.

[0073] The XRD measurement method was as follows: the phase composition of the sample was analyzed using a Rigaku Ultima IV X-ray powder diffractometer (Japan), with a CuKα ray source. Nickel filter, 2θ scanning range 3°-75°, operating voltage 35KV, current 25mA, scanning rate 10° / min.

[0074] In this invention, the contact angle measuring instrument is a DSA100 from KRUSS GmbH, Germany. The angle θ between the tangent line drawn from the gas-liquid-solid interface at the point of contact between the gas, liquid, and solid phases and the solid-liquid boundary line passing through this contact point is the contact angle of the liquid on the solid surface. When the gas is air, the solid is modified MOF material, and the liquid is water, the measured contact angle is the contact angle between the modified MOF material and water. A larger contact angle indicates better relative hydrophobicity of the modified MOF catalyst.

[0075] In this invention, scanning electron microscope (SEM) images of the samples were taken using a Hitachi S-4800II scanning electron microscope. The instrument's accelerating voltage was 15 kV, and all samples underwent chrome plating before analysis.

[0076] In this invention, the instruments and methods for testing the average pore size, specific surface area, and pore volume of the samples are as follows: Physical adsorption using nitrogen gas was performed at -196℃ using a 3H-2000PM2 physical adsorption instrument to analyze the pore structure characteristics of each adsorbent material sample. The initial degassing conditions were: degassing at 150℃ for 6 hours. After obtaining the adsorption isotherm of nitrogen on the sample, the specific surface area was calculated using the BET (Brunauer-Emmett-Teller) method, and the pore volume and pore size distribution were calculated using the BJH (Barrett-Joyner-Halenda) method.

[0077] Conversion rate of 2,5-hexanedione % = (molar amount of 2,5-hexanedione participating in the reaction) / (molar amount of 2,5-hexanedione substrate) × 100%.

[0078] Yield % of the product 2,5-dimethyl-N-substituted pyrrole compound = (molar amount of 2,5-dimethyl-N-substituted pyrrole generated in the reaction) / (molar amount of the reaction substrate 2,5-hexanedione) × 100%.

[0079] The selectivity % of the product 2,5-dimethyl-N-substituted pyrrole = (molar amount of 2,5-dimethyl-N-substituted pyrrole produced in the reaction) / (molar amount of 2,5-hexanedione produced in the reaction) × 100%.

[0080] To facilitate understanding of the present invention, the following embodiments are provided. However, these embodiments are merely for the purpose of helping to understand the present invention and should not be regarded as specific limitations of the present invention.

[0081] Example 1

[0082] S1. Weigh 3g of trimesic acid and add it to a mixture of 70mL anhydrous ethanol and 40mL LDM, stirring thoroughly for 20min. Weigh 6g of copper nitrate trihydrate and dissolve it in 70mL H2O. Mix the two solutions together, stir thoroughly, and place the mixture in a reaction vessel. Crystallize at 85℃ for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash several times with ethanol. Drying is carried out in two stages: the first stage is at 75℃ for 4h, and the second stage is at 150℃ for 10h. Then, vacuum dry at 100℃ for 10h to obtain Cu-BTC.

[0083] S2. Weigh 0.6 g of benzimidazole (BzIm) and add it to 80 mL of methanol, stirring thoroughly to obtain a methanol solution. Weigh 1.2 g of Cu-BTC prepared in step S1 and add it to the methanol solution, controlling the rotation speed at 400-600 r / min. Then, add 0.8 g of triethylamine dropwise, stirring thoroughly for 6 h. Place the solution in a reaction vessel and crystallize at 80 °C for 16 h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with methanol. Drying is carried out in two stages. The first stage is at 75 °C for 4 h. After drying, soak it in dichloromethane for 48 h, changing the solution every 24 h. The second stage of drying is at 150 °C for 10 h. Then, vacuum dry at 100 °C for 10 h to obtain hydrophobic Cu-BTC-BzIm.

[0084] SEM images of samples Cu-BTC and Cu-BTC-BzIm are shown below. Figure 1 As shown, the SEM image of Cu-BTC is as follows: Figure 1 As shown in (a), the crystals are regular octahedrons with smooth surfaces, and the crystal size is 12-18 μm. The SEM image of Cu-BTC-BzIm is shown below. Figure 1 As shown in (b), the crystal form of Cu-BTC-BzIm did not change significantly, but there were clusters of flaky protrusions on the surface, thus forming a wrinkled outer surface.

[0085] pyridine desorption infrared spectroscopy of samples Cu-BTC and Cu-BTC-BzIm Figure 2 As shown, by Figure 2 The total acidity of Cu-BTC-BzIm was calculated to be 178.6 μmol·g. -1 The total acidity of Cu-BTC is 50.3 μmol·g. -1 .

[0086] Cu-BTC material is hydrophilic because its ligands are carboxylic acids. Figure 3 As shown in the figure. After modification with imidazole ligands containing benzene rings, the Cu-BTC-BzIm material exhibits certain hydrophobicity compared to Cu-BTC. The contact angle test results are shown in the figure. Figure 4As shown, the contact angle between Cu-BTC-BzIm and water is 78-81°.

[0087] The nitrogen adsorption-desorption curves of Cu-BTC and Cu-BTC-BzIm are as follows: Figure 5 As shown; among them, the specific surface area of ​​Cu-BTC is 1572.8 m². 2 ·g -1 External specific surface area: 43.1 m² 2 ·g -1 Total pore volume: 0.72 cm³ 3 ·g -1 0.62cm 3 ·g -1 ;

[0088] Cu-BTC-BzIm has a specific surface area of ​​1316.1 m². 2 ·g -1 External specific surface area: 78.8 m² 2 ·g -1 Total pore volume: 0.77 cm³ 3 ·g -1 0.38cm 3 ·g -1 Compared to Cu-BTC, Cu-BTC-BzIm material has a lower total specific surface area, but an increased external specific surface area and a smaller micropore volume, thus increasing the mesopore / macropore volume.

[0089] Example 2

[0090] S1. Weigh 3g of trimesic acid and add it to a mixture of 70mL anhydrous ethanol and 40mL LDM, stirring thoroughly for 20min. Weigh 6g of copper nitrate trihydrate and dissolve it in 70mL H2O. Mix the two solutions together, stir thoroughly, and place the mixture in a reaction vessel. Crystallize at 85℃ for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash several times with ethanol. Drying is carried out in two stages: the first stage is at 75℃ for 4h, and the second stage is at 150℃ for 10h. Then, vacuum dry at 100℃ for 10h to obtain Cu-BTC.

[0091] S2. Weigh 1.2 g of benzimidazole and add it to 80 mL of methanol, stirring thoroughly to obtain a methanol solution. Weigh the Cu-BTC prepared in step S1 and add it to the methanol solution, controlling the rotation speed at 400-600 r / min. Then, add 0.8 g of triethylamine dropwise, stirring thoroughly for 6 h. The solution is then placed in a reaction vessel and crystallized at 80 °C for 16 h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with methanol. Drying is carried out in two stages. The first stage is at 75 °C for 4 h. After drying, immerse it in dichloromethane for 48 h, changing the solution every 24 h. The second stage is at 150 °C for 10 h. Finally, vacuum dry at 100 °C for 10 h to obtain hydrophobic Cu-BTC-BzIm-2.

[0092] SEM image of Cu-BTC-BzIm-2 is shown below. Figure 6 As shown, the crystal surface has clusters of lamellar protrusions, forming a wrinkled outer surface, and in contrast... Figure 1 (b) The clustered, sheet-like protrusions are more densely packed.

[0093] The total acidity of Cu-BTC-BzIm-2 is 159.3 μmol·g. -1 It has a hydrophobic angle of 90° and a specific surface area of ​​1200.7 m². 2 ·g -1 External specific surface area: 61.5 m² 2 ·g -1 Total pore volume: 0.68 cm³ 3 ·g -1 0.35cm 3 ·g -1 .

[0094] Example 3

[0095] The method of Example 1 was followed, except that in step S2, 0.4g of benzimidazole was used instead of 0.6g of benzimidazole, and the other conditions were the same as in Example 1, to obtain Cu-BTC-BzIm-3.

[0096] The SEM image of Cu-BTC-BzIm-3 is similar to the Cu-BTC-BzIm morphology image of Example 1.

[0097] The total acidity of Cu-BTC-BzIm-3 is 175.5 μmol·g. -1 It has a hydrophobic angle of approximately 72° and a specific surface area of ​​1408.9 m². 2 ·g -1 External specific surface area: 55.2 m² 2 ·g -1 Total pore volume: 0.7 cm³ 3 ·g -1 0.49cm3 ·g -1 .

[0098] Example 4

[0099] The method of Example 1 was followed, except that in step S2, the amount of triethylamine used was 2.4 g; the other conditions were the same as in Example 1, and Cu-BTC-BzIm-4 was obtained.

[0100] The SEM image of Cu-BTC-BzIm-4 is similar to the Cu-BTC-BzIm morphology image of Example 1.

[0101] The total acidity of Cu-BTC-BzIm-4 is 147.1 μmol·g. -1 It has a hydrophobic angle of approximately 65° and a specific surface area of ​​1219.5 m². 2 ·g -1 External specific surface area: 50.7 m² 2 ·g -1 Total pore volume: 0.61 cm³ 3 ·g -1 0.37cm 3 ·g -1 .

[0102] Example 5

[0103] The method of Example 1 was followed, except that in step S2, 80 mL of toluene was used instead of 80 mL of methanol, and the other conditions were the same as in Example 1, to obtain Cu-BTC-BzIm-5.

[0104] The SEM image of Cu-BTC-BzIm-5 is similar to the Cu-BTC-BzIm morphology image of Example 1.

[0105] The total acidity of Cu-BTC-BzIm-5 is 166.2 μmol·g. -1 It has a hydrophobic angle of approximately 95° and a specific surface area of ​​1299.3 m². 2 ·g -1 External specific surface area: 89.2 m² 2 ·g -1 Total pore volume: 0.75 cm³ 3 ·g -1 0.32cm 3 ·g -1 .

[0106] Example 6

[0107] The method of Example 1 was followed, except that in step S2, 80 mL of ethanol was used instead of 80 mL of methanol, and the other conditions were the same as in Example 1, to obtain Cu-BTC-BzIm-6.

[0108] The SEM image of Cu-BTC-BzIm-6 is similar to the Cu-BTC-BzIm morphology image of Example 1.

[0109] The total acidity of Cu-BTC-BzIm-6 is 177.9 μmol·g. -1 It has a hydrophobic angle of approximately 82° and a specific surface area of ​​1357.8 m². 2 ·g -1 External specific surface area: 80.7 m² 2 ·g -1 Total pore volume: 0.78 cm³ 3 ·g -1 0.41cm 3 ·g -1 .

[0110] Example 7

[0111] The method of Example 1 was followed, except that in step S2, 0.6 g of 2-methylbenzimidazole was used instead of benzimidazole, and the other conditions were the same as in Example 1, to obtain Cu-BTC-BzIm-7.

[0112] The SEM image of Cu-BTC-BzIm-7 is similar to the Cu-BTC-BzIm morphology image of Example 1.

[0113] The total acidity of Cu-BTC-BzIm-7 is 170.4 μmol·g. -1 It has a hydrophobic angle of approximately 86° and a specific surface area of ​​1309.2 m². 2 ·g -1 External specific surface area: 81.6 m² 2 ·g -1 Total pore volume: 0.76 cm³ 3 ·g -1 0.39cm 3 ·g -1 .

[0114] Example 8

[0115] The method of Example 1 was followed, except that in step S2, 0.6g of 5,6-dimethylbenzimidazole was used instead of benzimidazole, and the other conditions were the same as in Example 1, to obtain Cu-BTC-BzIm-8.

[0116] The SEM image of Cu-BTC-BzIm-8 is similar to the Cu-BTC-BzIm morphology image of Example 1.

[0117] The total acidity of Cu-BTC-BzIm-8 is 165.1 μmol·g. -1 It has a hydrophobic angle of approximately 91° and a specific surface area of ​​1281.1 m².2 ·g -1 External specific surface area: 82.3 m² 2 ·g -1 Total pore volume: 0.69 cm³ 3 ·g -1 0.34cm 3 ·g -1 .

[0118] Example 9

[0119] The method of Example 1 is followed, except that in step S1, 2.4g of terephthalic acid is used instead of 3g of trimesic acid, and the other conditions are the same as in Example 1, to obtain Cu-BDC-BzIm.

[0120] The crystal exhibits a multifaceted cubic crystal form.

[0121] The total acidity of Cu-BDC-BzIm is 125.8 μmol·g. -1 It has a hydrophobic angle of approximately 70° and a specific surface area of ​​1003.5 m². 2 ·g -1 External specific surface area: 35.4 m² 2 ·g -1 Total pore volume: 0.59 cm³ 3 ·g -1 0.3cm 3 ·g -1 .

[0122] Example 10

[0123] S1. Weigh 2.4g of terephthalic acid and add it to a mixture of 70mL anhydrous ethanol and 40mL LDM, stirring thoroughly for 20min. Weigh 7.38g of zinc nitrate hexahydrate and dissolve it in 70mL H2O. Mix the two solutions together, stir thoroughly, and place the mixture in a reaction vessel for crystallization at 85℃ for 20h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash several times with ethanol. Drying is carried out in two stages: the first stage is at 75℃ for 4h, and the second stage is at 150℃ for 10h. Then, vacuum dry at 100℃ for 10h to obtain Zn-BDC.

[0124] S2. Weigh 0.6 g of benzimidazole (BzIm) and add it to 80 mL of methanol, stirring thoroughly to obtain a methanol solution. Weigh 1.2 g of Zn-BDC prepared in step S1 and add it to the methanol solution, controlling the rotation speed at 400-600 r / min. Then, add 0.8 g of triethylamine dropwise, stirring thoroughly for 6 h. Place the solution in a reaction vessel and crystallize at 80 °C for 16 h. After crystallization, cool to room temperature, centrifuge to remove the mother liquor, and wash with methanol. Drying is carried out in two stages. The first stage is at 75 °C for 4 h. After drying, soak it in dichloromethane for 48 h, changing the solution every 24 h. The second stage of drying is at 150 °C for 10 h. Then, vacuum dry at 100 °C for 10 h to obtain hydrophobic Zn-BDC-BzIm.

[0125] The crystal exhibits a multifaceted cubic crystal form.

[0126] The total acidity of Zn-BDC-BzIm is 143.2 μmol·g. -1 It has a hydrophobic angle of approximately 79° and a specific surface area of ​​1689.4 m². 2 ·g -1 External specific surface area: 85.3 m² 2 ·g -1 Total pore volume: 0.89 cm³ 3 ·g -1 0.52cm 3 ·g -1 .

[0127] Examples 11-20

[0128] Using 2,5-hexanedione and aniline as substrates and methanol as the reaction solvent, 0.2 g of the catalyst from Examples 1-10, 2.0 g of 2,5-hexanedione, 1.2 g of aniline, and 10 g of methanol were added to a high-pressure reactor equipped with a stirrer. Nitrogen gas at 1 MPa was introduced to prevent boiling of the organic solvent. The temperature was raised to the preset temperature using a programmed heating mantle, and then stirred magnetically. The reaction was carried out at 150 °C for 6 h. The conversion rate of 2,5-hexanedione and the yield of the target product 2,5-dimethyl-1-phenylpyrrole were analyzed and are shown in Table 1.

[0129] Table 1 Catalytic evaluation results of Examples 11-20

[0130]

[0131] Example 21

[0132] The method of Example 11 is the same, except that the amount of catalyst used is 0.1g, and the other conditions are the same as in Example 11.

[0133] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 97.1%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.8%.

[0134] Example 22

[0135] The method of Example 11 is the same, except that the amount of catalyst used is 0.5g, and the other conditions are the same as in Example 11.

[0136] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 98.9%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 98.5%.

[0137] Example 23

[0138] The method of Example 11 is the same, except that the reaction is carried out at 180°C for 6 hours, while the other conditions are the same as in Example 11.

[0139] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 99.7%; the yield of the target product 2,5-dimethyl-1-benzylpyrrole was 97.2%.

[0140] Example 24

[0141] The method of Example 11 is the same, except that the reaction is carried out at 120°C for 6 hours, while the other conditions are the same as in Example 11.

[0142] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 96.8%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 98.7%.

[0143] Example 25

[0144] The method of Example 11 is the same as that of Example 11, except that the reaction is carried out at 150°C for 12 hours.

[0145] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 99.8%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.1%.

[0146] Example 26

[0147] The method of Example 11 is the same, except that the amount of aniline used is 0.6g, and the other conditions are the same as in Example 11.

[0148] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 93.2%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 92.8%.

[0149] Example 27

[0150] The method of Example 11 is the same as that of Example 11, except that tetrahydrofuran is used instead of methanol.

[0151] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 97.6%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 96.9%.

[0152] Example 28

[0153] The method of Example 11 is the same as that of Example 11, except that toluene is used instead of methanol.

[0154] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 98.2%; the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 97.8%.

[0155] Example 29

[0156] The method of Example 11 is the same, except that the amine compound is m-toluidine, and the other conditions are the same as in Example 11.

[0157] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 98.1%; the yield of the target product 2,5-dimethyl-1-m-phenylmethyl-1-H-pyrrole was 80.3%.

[0158] Example 30

[0159] The method of Example 11 is the same, except that the amine compound is p-methoxyaniline, and the other conditions are the same as in Example 11.

[0160] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 97.2%; the yield of the target product 1-(4-methoxyphenyl)-2,5-dimethyl-1H-pyrrole was 78.5%.

[0161] Example 31

[0162] The method of Example 11 is the same, except that the amine compound is m-chloroaniline, and the other conditions are the same as in Example 11.

[0163] Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 99.2%; the yield of the target product 1-(3-chlorophenyl)-2,5-dimethyl-1H-pyrrole was 93.4%.

[0164] Comparative Example 1

[0165] Using 2,5-hexanedione and aniline as substrates and methanol as the reaction solvent, 0.2 g of HY(37), 2.0 g of 2,5-hexanedione, and 1.2 g of aniline were added to a high-pressure reactor equipped with a stirrer. Nitrogen gas at 1 MPa was introduced to prevent boiling of the organic solvent. The temperature was raised to the preset temperature using a programmed heating mantle, and then stirred magnetically. The reaction was carried out at 150 °C for 6 h. Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 88.5%, and the yield of the target product, 2,5-dimethyl-1-phenylpyrrole, was 72.7%.

[0166] Comparative Example 2

[0167] Using 2,5-hexanedione and aniline as substrates and methanol as the reaction solvent, 0.2 g of H-Beta(100), 2.0 g of 2,5-hexanedione, and 1.2 g of aniline were added to a high-pressure reactor equipped with a stirrer. Nitrogen gas was introduced at 1 MPa to prevent boiling of the organic solvent. The temperature was raised to the preset temperature using a programmed heating mantle, and the mixture was stirred magnetically. The reaction was carried out at 150 °C for 6 h. Analysis of the reaction solution showed that the conversion rate of 2,5-hexanedione was 72.5%, and the yield of the target product, 2,5-dimethyl-1-phenylpyrrole, was 66.9%.

[0168] Comparative Example 3

[0169] The method of Example 11 was followed, except that Cu-BTC prepared according to the method of Example 1 was used instead of Cu-BTC-BzIm, and the other conditions were the same as in Example 11. The reaction solution was analyzed and found that the conversion rate of 2,5-hexanedione was 82.7% and the yield of the target product 2,5-dimethyl-1-phenylpyrrole was 73.8%.

[0170] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. The application of modified metal-organic framework materials in the catalytic preparation of 2,5-dimethyl-N-substituted pyrrole compounds, characterized in that, The modified metal-organic framework material includes: Metal center; and At least two organic ligands coordinated to at least two binding sites of the metal center to form a network structure with at least partial crystallization having multiple internal pores; The modified metal-organic framework material crystal has a wrinkled outer surface, and the contact angle between the modified metal-organic framework material and water is 40-120°. The organic ligand includes a first organic ligand and a second organic ligand; the first organic ligand is selected from at least one of pyromellitic acid, terephthalic acid, phthalic acid, biphenyl-3,4,5-tricarboxylic acid, 1,4-naphthalenedicarboxylic acid, biphenyl dicarboxylic acid and 3,3,5,5-biphenyltetracarboxylic acid; The second organic ligand is selected from at least one of benzimidazole, 2-methylbenzimidazole, 5,6-dimethylbenzimidazole, 2-(2-hydroxybenzyl)benzimidazole, 2-aminobenzimidazole, and 2-(4'-thiazole)benzimidazole; The metal at the metal center is selected from Zn and / or Cu.

2. The application according to claim 1, wherein, The modified metal-organic framework material has a contact angle of 40-100° with water; and / or The modified metal-organic framework material has clusters of sheet-like protrusions distributed on its crystal surface, forming a wrinkled outer surface.

3. The application according to claim 1 or 2, wherein, The total acidity of the modified metal-organic framework material is 30-500 µmol•g. -1 ; and / or The modified metal-organic framework material has a total specific surface area of ​​900-1800 m². 2 •g -1 ; and / or The total pore volume of the modified metal-organic framework material is 0.4-1.0 cm³. 3 •g -1 .

4. The application according to claim 1 or 2, wherein, The total acidity of the modified metal-organic framework material is 40-400 µmol•g. -1 ; and / or The modified metal-organic framework material has a total specific surface area of ​​40-200 m². 2 •g -1 ; and / or The total pore volume of the modified metal-organic framework material is 0.2-0.9 cm³. 3 •g -1 .

5. The application according to claim 1 or 2, wherein, The preparation method of the modified metal-organic framework material includes the following steps: S1. Dissolve the soluble metal salt and organic ligand I in solvent I, crystallize, separate, and first dry to obtain MOF material formed by metal and organic ligand I; S2. Contact the MOFs material from step S1 with a solution containing organic ligand II and an alkaline substance; separate, wash, and perform a second drying to obtain the modified metal-organic framework material; organic ligand I is the first organic ligand; organic ligand II is the second organic ligand.

6. The application according to claim 5, wherein, In step S1, the molar ratio of the soluble metal salt to organic ligand I is 1:0.2-5; and / or In step S1, the ratio of solvent I to soluble metal salt is 5-100 mL solvent I / 1.0 g soluble metal salt; and / or In step S2, the molar ratio of MOF materials to organic ligand II is 1:(0.01-5); and / or In step S2, the molar ratio of MOF materials to alkaline substances is 1:(0.01-3); and / or In step S2, the solvent in the solution containing organic ligand II and the alkaline substance is solvent II, which is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, tetrahydrofuran, methanol, ethanol, acetone, dichloromethane, toluene, and ethylbenzene; and / or In step S2, the alkaline substance is selected from at least one of triethylamine, trimethylamine, diisopropylethylamine, diethylamine, n-propylamine, n-butylamine, di-n-butylamine, ammonia, and aniline.

7. The application according to claim 6, wherein, The mass ratio of MOF material to solvent II is 1:(2-200).

8. The application according to claim 5, wherein, Step S2 further includes immersing the washed solid in solvent III, wherein solvent III is selected from at least one of methanol, ethanol, dichloromethane and acetone.

9. The application according to claim 8, wherein, Soaking conditions include: soaking temperature of 0-50℃; and / or The mass ratio of solid to solvent III is 1:10-300; and / or Soaking time is 10-96 hours, and solvent III should be replaced every 2-24 hours.

10. The application according to claim 5, wherein, In step S1, the crystallization conditions include: a crystallization temperature of 30-200℃ and a crystallization time of 3-44h; and / or In step S1, the first drying conditions include: a drying temperature of 70-200℃ and a drying time of 2-48h; and / or In step S2, the contact conditions include: a contact temperature of 30-180℃ and a contact time of 3-30h; In step S2, the second drying conditions include: a drying temperature of 70-200℃ and a drying time of 2-48h.

11. The application according to claim 10, wherein, In step S1, the crystallization conditions include: a crystallization temperature of 50-160℃ and a crystallization time of 5-24h; and / or In step S1, the first drying is a step-by-step drying process. The first drying condition includes a temperature of 70-100℃ and a time of 1-24 hours; the second drying condition includes a temperature of 120-200℃ and a time of 1-24 hours; and / or In step S2, the contact conditions include: a contact temperature of 50-110℃ and a contact time of 6-20 hours; and / or In step S2, the second drying is a step-by-step drying. The first drying conditions include a temperature of 70-100℃ and a time of 1-24h; the second drying conditions include a temperature of 120-200℃ and a time of 1-24h.

Citation Information

Patent Citations

  • Double-ligand metal organic framework material as well as preparation method and application thereof

    CN114479096A